Взаємодія архітектури і середовища у найвидатнішому творі Ніва Брауна - Джигіль, Юрій; Dzhyhil, Yuriy (Видавництво Львівської політехніки, 2023)
Розглянуто витоки особливих творчих методів роботи британського архітектора Ніва Брауна (1929-2018 рр.). Розкриті глибинні ідеї, які автор заклав в архітектурно-просторові рішення найвідомішого з своїх творів – житлового комплексу Alexandra Road Estate в районі Камден (Camden Town) у Лондоні (Великобританія). Зокрема, розкрита роль соціального контексту у формуванні житла і показана взаємодія архітектури з міським середовищем. Виявлена актуальність ідей Ніва Брауна та важливість їх адаптації в сучасне житлове будівництво. Зроблений висновок - твір Ніва Брауна Alexandra Road Estate можна вважати одним з найяскравіших прикладів архітектурного модернізму у житловій архітектурі 70-х років ХХ ст. Ідеї Ніва Брауна про напрямки розвитку житлової архітектури є актуальними і у наш час, особливо в сучасних реаліях України, коли висувається багато пропозицій її повоєнної відбудови.

The article explores the origins of unique creative methods of the British architect Neave Brown (1929-2018). The deep ideas that the author laid in the architectural and spatial solutions of the most famous of his works - the Alexandra Road Estate residential complex in the Camden Town district of London (Great Britain) are revealed. In particular, the role of the social context in the formation of housing is revealed and the interaction of architecture with the urban environment is demonstrated. The relevance of Neave Brown's ideas and the importance of their adaptation in modern residential construction have been revealed. He singled out the important project tasks that affect the quality of the architectural environment. To achieve this, efforts should be aimed at ensuring: of favorable physical condition of the environment - protection against noise and vibrations, insolation and natural lighting, landscaping, etc.; conditions of residents’ socialization - for their service, communication, physical activity, care of the adjoining territory, etc.; safe, convenient, comfortable living conditions in apartments. Neave Brown defined social housing as rational, functionally expedient, financially affordable. But that didn't mean dwellings had to be cheap. Environmental degradation and social losses due to poor design decisions lead to premature deterioration of relatively new buildings. That is unacceptable from the point of view of modern requirements for saving fossil resources, reducing emissions and rational use of nature. Also, the Alexandra Road Estate project solved an important problem of rational and competent use of the territory previously unsuitable for development. The residential complex had a population density of 210 people per acre, which rivaled high-rises. The conclusion is drawn - by Neave Braun's project of Alexandra Road Estate can be considered one of the most amazing examples of architectural modernism in residential architecture of the 70s of the XX century. Neave Brown's ideas regarding the directions of development of residential architecture are still relevant today, especially in the realities of Ukraine, when many proposals for its post-war reconstruction are put forward.
The interaction of architecture and environment in Neave Brown’s most outstanding creation
Keywords: архітектура; дизайн; середовище; соціальне житло; шумозахист; architecture; design; environment; social housing; noise protection; 728.1